Relationship between personality traits and work performance of paddy farmers in granary areas in Malaysia - Ak. Mohiddin, Dk. Norhajijah (2021)
Rice is a staple grain and a widely consumed grain in Malaysia. Malaysia's population in 2019 was estimated at 32.6 million, which increased by 0.2 million from the previous year. Recently, Malaysia's rice self-sufficiency level lingered between 60 – 70%. While in old granary areas, the production reaches around 50% only, which is still low after establishing old granaries in 1967. Thus, this research purpose was to avoid repeating the low performance of new granary areas. Apart from that, based on the theory of work performance by The Iceberg Model of Competencies by Spencer and Spencer (1993), this study contributes by testing four new personality traits that Hassan (2012) found in North West Selangor using quantitative methods. Therefore, the producer's personality traits with their work performance in granary areas examine to improve rice production in granary areas. Among all aspects, Farmer's personality traits are one-factor determining yield's success in any granary area. This research study involved unrevealed personality traits of producers in old and three new granary areas that have not been carried out. Seven personality traits studied will develop paddy farmers to become successful individuals and entrepreneurs. Personality traits reflected farmers' characteristics, the pattern of thoughts, feelings, and behaviours. Moreover, work performance interpreted farmers' personalities or actions relevant to the business goals. The relationship of personality Traits towards work performance is the effectiveness of individual behaviours contributing to organizational objectives. The objectives of this study were to determine the level of personality traits of paddy farmers, determine the relationship between personality traits and work performance, and determine the most contributed factors to paddy farmers' work performance in Malaysia granary areas. This study adopted a quantitative research method and questionnaires as a research tool. Then, a stratified randomized sampling technique was applied to meet 828 respondents. Data collected was analyzed by using SPSS correlation and multiple regression coefficient analysis. The findings on six granary areas were that discipline has the highest impact on work performance among all personality traits. All seven personality traits recorded a moderate correlation with work performance. The findings in old granary areas recorded five high-level personality traits (discipline, information seeking, investment, decision making, and networking) and moderate problem solving and risk taking. Whereas in new granary areas, (discipline, information seeking, and networking) stated high level while (risk taking, problem solving, willingness to invest, and decision making) at a moderate level. Results revealed that all seven personality traits positively correlate with work performance in all granary areas. In old granary areas, the analysis showed discipline having a more significant impact on work performance. Therefore, paddy farmers in the old group will achieve better work performance with higher discipline practices. Following new granary areas, networking was the most contributed personality trait towards work performance. Broader connections practices in new granary areas may significantly improve work performance. Multiple regression analysis in all granary results showed significant differences in five personality traits: information seeking, problem solving, decision making, networking, and discipline. These variables explain the 47.9% variance of work performance (Adj. R²=0.479). Likewise, in old granary areas, five personality traits of information seeking, problem solving, investment, networking, and discipline were significant differences in work performance. These variables explain a 37.2% variance in work performance (Adj. R²=0.372). Meanwhile, only three variables with significant differences in new granary areas were problem solving, networking and discipline. Three variables explain a 42.6% variance in work performance (Adj. R²=0.426). Conclusively, discipline in all granaries and old granary areas and networking in new ones are the most influential personality traits in improving work performance. The implication of these findings will benefit the extension field by providing details on seven personality traits that need improvement in paddy farmers. Finally, this research supports the sixth objective in the National Agro-Food Policy 2011- 2020 for the rice sector by strengthening the institutional management of paddy and rice. This research study will aid Integrated Agricultural Development Area in improving the personality traits of paddy farmers in old granary areas. At the same time, it enhances personality traits in new granary areas, which will strengthen Malaysia's "rice bowl" as a whole.